The way things work. Flight [videorecording (DVD)] - Zamora, Diego; Macaulay, David (Schlessinger Media, 2003)
When a mammoth delivering canvas awnings gets lifted off the ground by the wind, the Mammoth Islanders discover the power of the wind. The Islanders experiment and eventually learn the right combination of the four forces involved in flight: gravity, lift, thrust, and drag.